Analysis of the chromosphere and corona of low-activity early-M dwarfs. Issue Volume 15:Issue S354(2019) (June 2019) - Scandariato, Gaetano; Álvarez, E. González; Maldonado, J.; Mascareño, A. Suárez; Perger, M.
Abstract: While most of the exoplanets have been found orbiting around solar-type stars, low-mass stars have recently been recognized as ideal exo-life laboratory. Currently, stellar activity is one of the limiting factors for the characterization of Earth-twins and for assessing their habitability: understanding the activity of M dwarfs is thus crucial. In this contribution I present the spectroscopic analysis of the quiet early-M dwarfs monitored within the HADES (HArps-n red Dwarf Exoplanet Survey) radial velocity survey. The spectra allow us to analyze simultaneously the Ca ii H&K doublet and the Hydrogen Balmer series, while the intensive follow up gives us a large number of spectra ( 100) for each target. We complement this dataset with ground-based follow-up photometry and archival X-ray data. I present our results on the activity-rotation-stellar parameters and flux-flux relationships, and discuss the correlation of emission fluxes at low activity levels and the evolution timescales of active regions.